Characteristics of flax oil and milk mixture - Chen, Cunshe; Liu, Ping; Li, Mengfei; Zhang, Xin (International Journal of Agricultural and Biological Engineering, 2022)
In order to develop milk products both with better taste and more health benefits, it is studied that a blended system of dairy products and flax oil based on the Budwig diet. The amounts of flax oil added to the pure milk or yogurt were varied and the system was fully mixed without adversely affecting the flavor. The effects of flax oil addition on the frictional and rheological properties of different dairy products were investigated, and the optimal addition ratio was determined combined with the sensory evaluation. The experimental results showed that the addition ratio of flax oil significantly affected the friction characteristics and rheological properties of dairy products, in which the friction coefficient of the mixture tended to decrease as the addition of flax oil increased, and with the added increase the viscosities of both ordinary yogurt mixture and pure milk mixture tended to increase. Furthermore, based on physical characteristics and sensory properties the optimal addition ratios of flax oil to pure milk, ordinary yogurt, and non-fat yogurt are obtained, which are 2.5wt%, 2.5wt%, and 5wt%, respectively. The study provides a quantified analysis way for the additions to the dairy products and the obtained data can be used for reference in production. Keywords: rheology, tribology, flax oil, milk, yogurt, mixture, characteristics DOI: 10.25165/j.ijabe.20221504.7108 Citation: Chen C S, Liu P, Li M F, Zhang X. Characteristics of flax oil and milk mixture. Int J Agric & Biol Eng, 2022; 15(4): 264–270.